Effect of Drying Operating Conditions on Canola Oil Tocopherol Content - Daniela Laoretani; María Fernández; Guillermo Crapiste; Susana Nolasco (MDPI AG, 2014)
The aim of this work was to evaluate two operating parameters of seed drying (temperature and initial moisture content) on the tocopherol content of canola oil. The raw material was characterized by moisture, oil, protein, crude fiber and ash content. Seeds at 13.6% and 22.7% moisture content (dry basis, db) were dried at temperatures in the range of 35-100 °C to a safe storage moisture of 7% db. Oil was extracted from each treated sample. The oil extracted from the samples dried at the extreme temperatures was analyzed by means of the acidity value, peroxide index and fatty acid composition, finding no significant differences among treatments or among untreated and treated samples. Tocopherol contents in the oils obtained for all the assayed temperatures were determined. Differences were found for the samples with 22.7% (db) initial moisture content. Except at 35 °C, temperature affected negatively the oil tocopherol content. However, when 13.6% (db) moisture seeds were processed, no significant differences were observed in the amount of this minor oil component among assays.